2023
DOI: 10.3390/diagnostics13101803
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of the Neutropenia Associated with GSD1b and G6PC3 Deficiency with SGLT2 Inhibitors

Abstract: Glycogen storage disease type Ib (GSD1b) is due to a defect in the glucose-6-phosphate transporter (G6PT) of the endoplasmic reticulum, which is encoded by the SLC37A4 gene. This transporter allows the glucose-6-phosphate that is made in the cytosol to cross the endoplasmic reticulum (ER) membrane and be hydrolyzed by glucose-6-phosphatase (G6PC1), a membrane enzyme whose catalytic site faces the lumen of the ER. Logically, G6PT deficiency causes the same metabolic symptoms (hepatorenal glycogenosis, lactic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…Regarding the number of white blood cells, two clinical trials show the therapeutic role of empagliflozin in neutropenia. 111 , 112 This issue has also been confirmed by Veiga-da-Cunha et al 113 In relation to canagliflozin, another clinical trial showed the opposite effect and that treatment with canagliflozin causes a decrease in white blood cells. 114 In order to determine the role of this drug in relation to the number of white blood cells, large clinical trials are needed.…”
Section: Blood Components and Electrolytesmentioning
confidence: 62%
“…Regarding the number of white blood cells, two clinical trials show the therapeutic role of empagliflozin in neutropenia. 111 , 112 This issue has also been confirmed by Veiga-da-Cunha et al 113 In relation to canagliflozin, another clinical trial showed the opposite effect and that treatment with canagliflozin causes a decrease in white blood cells. 114 In order to determine the role of this drug in relation to the number of white blood cells, large clinical trials are needed.…”
Section: Blood Components and Electrolytesmentioning
confidence: 62%
“… 19 Recent studies have indicated that empagliflozin, a sodium glucose co-transporter 2 inhibitor, represents a safe and promising alternative for treating neutropenia in individuals with GSD1b, IBD, and neutropenia. 20 In this study, empagliflozin was prescribed to Patient 2 at the age of 6 years, leading to a gradual discontinuation of G-CSF. Subsequently, the patient experienced an improvement in gastrointestinal symptoms, with a normal ANC observed during the last follow-up and no reported adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, empagliflozin, an SGLT2 inhibitor frequently used to treat type 2 diabetes, has successfully resolved neutrophil defects in patients with G6PC3 deficiency by lowering the 1,5-AG blood concentrations 30,33,34 . Along with the use of this highly effective, safe, and easy-to-take oral alternative to granulocyte-colonystimulating factor (G-CSF) injections, early disease diagnosis may improve outcomes of G6PC3 deficient patients 35,36 .…”
Section: Discussionmentioning
confidence: 99%